The individual responsibility in the international criminal law (Al-Mansour Journal, 2022)
The international legal provisions on war crimes and crimes against humanity have been adopted and developed within the framework of international humanitarian law, or the law of armed conflict. In search the need to determine individual responsibility, Article 25 of the Statute of the International Criminal Court (ICC) now contains a detailed regulation of individual criminal responsibility. That military commanders and other persons occupying positions of superior authority may be held criminally responsible for the unlawful conduct of their subordinates is a well-established norm of customary and conventional international law. This criminal liability may arise either out of the positive acts of the superior (sometimes referred to as "direct" command responsibility) or from his culpable omissions ("indirect" command responsibility or command responsibility). Thus, a superior may be held criminally responsible not only for ordering, instigating or planning criminal acts carried out by his subordinates, but also for failing to take measures to prevent or repress the unlawful conduct of his subordinates. A military commander is responsible as a participant or an instigator if, by not taking measures against subordinates who violate the law of war, he allows his subordinate units to continue to commit the acts.
Keywords: international humanitarian law; International Criminal Court; law of armed conflict